Digital Transformation in Green HRM: Implementation of HR Analytics to Improve HR Sustainability in Manufacturing Companies in Bandung City - Ali, Nuraeni; Wahyuni Milang, Sri; Fajarwaty A. Sagaf, Fatma; Ladjin, Nurjanna (Yayasan Pendidikan Belajar Berdikari, 2025)
This study aims to analyze the influence of Green Human Resource Management (Green HRM) and Implementation of HR Analytics on Employee Green Behavior and its implications for Sustainable Human Resource Management (Sustainable HRM). Using quantitative methods with multiple linear regression analysis, this study involved 98 respondents from companies in the green industry sector. The results showed that Green HRM and Implementation of HR Analytics simultaneously and partially had a significant effect on Employee Green Behavior with an F value of 1707.554 and R² of 97.3%. However, when the three variables (Green HRM, Implementation of HR Analytics, and Employee Green Behavior) were tested against Sustainable HRM, the results showed a significant effect simultaneously, but not partially significant, with an F value of 35.559 and R² of 53.2%. The conclusion of this study indicates that although green HR policies and the use of HR analytics are effective in encouraging employee green behavior, sustainable HRM requires the support of other factors beyond the model studied. Therefore, this study recommends further exploration of external factors and strategic policies that can support the implementation of Sustainable HRM as a whole.